IgG-seq identifies immune-reactive enteric bacteria in Crohn’s disease with spondyloarthritis - Grace A. Maldarelli; Maeva Metz; Seun Oguntunmibi; Nancy Tran; Grace Xiang; Dana Lukin; Ellen J. Scherl; Randy S. Longman (Gut Microbes)
Joint inflammation is the most common extraintestinal manifestation of Crohn’s disease (CD). Although alterations in the enteric microbiota are described in CD with spondyloarthritis (CD-SpA), it is not known whether distinct taxa serve as markers for clinical subtypes of axial (AxSpA) or peripheral SpA (pSpA) in CD. Moreover, it is not yet known whether these taxa generate a specific systemic IgG response. Here, we sequenced the fecal microbiome from 106 individuals (44 CD, 39 CD-SpA, 14 CD-AxSpA, and 9 healthy controls [HC]). This unique cohort revealed distinct taxonomic compositions of CD and CD-SpA compared to HC and demonstrates that the composition of the CD-AxSpA microbiome is distinct from that of CD-pSpA. Using autologous serum, we identified enteric bacteria recognized by serum IgG and demonstrate differences in the IgG coating index of specific bacterial genera associated with CD-SpA. The IgG coating index of Mediterraneibacter gnavus differentiated patients with CD-pSpA and is positively associated with joint disease activity. This work illustrates divergent microbiome compositions in CD-SpA subtypes, as well as the recognition of distinct enteric bacteria by serum IgG with the potential to serve as a marker of joint inflammation in CD.